The Role of Madrasah Principal Leadership in Enhancing Institutional Quality in Islamic Senior High Schools - Muli Prima Aldi M; Tika Widiyan; Juni Erpida Nasution; Leni Fitrianti; Farida Nur Hidayah (Journal of Educational Management Research, 2026)
This study aims to analyze the leadership of madrasah principals in improving institutional quality at Islamic senior high schools. A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews, and document analysis. The findings indicate that the principal’s leadership was categorized as optimal, achieving a performance score of 78.57%, which reflects effective practices in curriculum development, teacher supervision, school management, and student development programs. Supporting factors for institutional quality improvement include the principal’s strong commitment to quality enhancement, effective communication, and collaborative relationships within the madrasah community. However, several challenges were identified, particularly limited educational facilities, constraints in human resources, and insufficient monitoring of teacher performance. The implications of this study suggest that strengthening leadership capacity, improving resource allocation, and implementing systematic teacher performance evaluation are essential strategies for enhancing institutional quality in Islamic senior high schools. These findings contribute to the understanding of effective madrasah leadership practices and provide practical insights for policymakers and school leaders seeking to improve educational quality in Islamic educational institutions.